2022
DOI: 10.1186/s13578-022-00769-8
|View full text |Cite
|
Sign up to set email alerts
|

BRD4 inhibitor GNE987 exerts anti-cancer effects by targeting super-enhancers in neuroblastoma

Abstract: Background Neuroblastoma (NB) is a common extracranial malignancy with high mortality in children. Recently, super-enhancers (SEs) have been reported to play a critical role in the tumorigenesis and development of NB via regulating a wide range of oncogenes Thus, the synthesis and identification of chemical inhibitors specifically targeting SEs are of great urgency for the clinical therapy of NB. This study aimed to characterize the activity of the SEs inhibitor GNE987, which targets BRD4, in N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 67 publications
1
13
0
Order By: Relevance
“…C-Myc is a well-studied proto-oncogene; it acts as a master regulator of cell proliferation, and its upregulation has been demonstrated in GBM [11]. In this study, we also found that GNE987 interfered with C-Myc protein level in GBM cells, indicating that in GBM, GNE987 can exert an antitumor effect by inhibiting the Myc pathway, similar results also appear in neuroblastoma [7].…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…C-Myc is a well-studied proto-oncogene; it acts as a master regulator of cell proliferation, and its upregulation has been demonstrated in GBM [11]. In this study, we also found that GNE987 interfered with C-Myc protein level in GBM cells, indicating that in GBM, GNE987 can exert an antitumor effect by inhibiting the Myc pathway, similar results also appear in neuroblastoma [7].…”
Section: Discussionsupporting
confidence: 82%
“…growth and increases apoptosis in neuroblastoma [7] and AML [8]. However, its anti-tumor activity and underlying mechanism in GBM are unavailable to date.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…ADAMTS15 is used to predict the survival of human breast carcinoma with the inhibitory functions to tumor growth and invasion of colorectal cancers ( Porter et al., 2006 ; Viloria et al., 2009 ). The high FAM163A expression is associated with short survival time in hepatocellular carcinoma and affects the occurrence and development of neuroblastoma ( Chen et al., 2022 ; Qiao et al., 2019 ). The methylation status of CDO1 was specifically high in small bowel cancer (SBC) ( Kojima et al., 2019 ), which indicates it is a biomarker of SBC.…”
Section: Discussionmentioning
confidence: 99%